Capital Structure, Organizational Slack and Sustainability Reporting In Islamic Bank of Indonesia, Qatar and Bahrain - Niswah, Milananda Ainun; Falikhatun, Falikhatun (Institut Agama Islam Negeri Madura, 2021)
This research aims to analyze the effects of capital structure and organizational slack on sustainability reporting in Islamic banks of Indonesia, Qatar, and Bahrain. The capital structure variable consists of leverage and investment account holders, while the organizational slack variable consists of available slack and recoverable slack. Analysis content that used to measure the disclosure of sustainability reporting based on the AAOFII index consisting of 78 items. The observation data used were 120 observations consisting of 26 Islamic banks on Indonesia, Qatar, and Bahrain for the period 2014 to 2018 with a purposive sampling method. The results showed that there was a positive influence between leverage and a negative effect between investment account holders on sustainability reporting. This study also found a positive relationship between available slack and there was no significant effect between recoverable slack on sustainability reporting.